Differences In The Financial Performance Of Transportation Companies On The Indonesia Stock Exchange During The Covid-19 Pandemic - Widowati, Dania; Nugroho, Hendrato (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2022)
The occurrence of the Covid-19 pandemic in Indonesia requires the Government to implement new policies in order to prevent transmission by imposing Large-Scale Social Restrictions (PSBB). The decline in community mobility results in fewer customers who will use the services of transportation companies. This case certainly has an impact on the revenues and profits of transportation companies. Under these conditions, the financial position as a performance description is very important to evaluate and measure the company's financial efficiency. This study aims to determine differences in the ratios of liquidity, solvency, and profitability of transportation companies on the Indonesia Stock Exchange before and during the Covid-19 pandemic. The sample used in this study is a transportation company that is listed on the Indonesia Stock Exchange and publishes financial statements consecutively for the 2018-2021 period, totaling 10 companies. This study uses secondary data obtained from sources www.idx.co.id and the company's official website, sampling is done by purposive sampling. The stages of analyzing the data used descriptive statistical tests, basic assumption tests, and different tests. The results of this study indicate that there are significant differences in the ratio of return on assets before and during the Covid-19 pandemic, but there are no significant differences in the current ratio, debt to asset ratio, net profit margin before and during the Covid-19 pandemic.